2009
DOI: 10.1681/asn.2008030325
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Inhibits Glycolysis in Ischemic Kidneys

Abstract: After ischemic renal injury (IRI), selective damage occurs in the S 3 segments of the proximal tubules as a result of inhibition of glycolysis, but the mechanism of this inhibition is unknown. We previously reported that inhibition of poly(ADP-ribose) polymerase-1 (PARP-1) activity protects against ischemia-induced necrosis in proximal tubules by preserving ATP levels. Here, we tested whether PARP-1 activation in proximal tubules after IRI leads to poly(ADP-ribosyl)ation of the key glycolytic enzyme glyceralde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 42 publications
3
73
0
Order By: Relevance
“…Activation of PARP1 is required for DNA repair, but excessive activation leads to necrotic cell death by depletion of intracellular ATP. 33,34 We previously reported that pharmacological and genetic inhibition of PARP1 can prevent kidney dysfunction, oxidative stress, inflammation, and tubular necrosis but not apoptosis after ischemia/ reperfusion 7,35 and cisplatin nephrotoxicity. 36 Furthermore, although bax/bak is generally regarded as an apoptosis inducer by regulating mitochondrial outer membrane permeabilization, recent evidence suggests that they may form the outer membrane channels of MPTP and contribute to necrotic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of PARP1 is required for DNA repair, but excessive activation leads to necrotic cell death by depletion of intracellular ATP. 33,34 We previously reported that pharmacological and genetic inhibition of PARP1 can prevent kidney dysfunction, oxidative stress, inflammation, and tubular necrosis but not apoptosis after ischemia/ reperfusion 7,35 and cisplatin nephrotoxicity. 36 Furthermore, although bax/bak is generally regarded as an apoptosis inducer by regulating mitochondrial outer membrane permeabilization, recent evidence suggests that they may form the outer membrane channels of MPTP and contribute to necrotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Persistent perfusion deficit in the medulla, limited anaerobic glycolytic capacity, and targeted inhibition of glycolysis in the proximal tubule cell (PTC) make the proximal straight tubule the most vulnerable tubular segment to ischemic injury. [4][5][6][7] Pathologically, IRI is characterized by apoptotic/necrotic cell death and inflammation in the outer medulla, which are proportional to the severity of renal ischemia. 8,9 Pro-and antiapoptotic signaling pathways in the PTC are precisely regulated by essential factors, such as p53 and its proapoptotic targets, BCL2 family proteins and caspases.…”
mentioning
confidence: 99%
“…Under stress conditions, GAPDH undergoes an oxidative inhibition, enabling the cells to redirect their carbohydrate flux from glycolysis to the pentose phosphate pathway, generating the reducing NADPH and protecting the cells [47]. Oxidative stress-induced DNA strand breaks activate the DNA repair enzyme poly(ADP-ribose) polymerase-1, which inactivates GAPDH by ADP-ribosylation and creating energy deficits and driving the cells towards accelerated cell death [48,49]. Thus, GAPDH relays the stress signals and regulates the ATP production to control the viable population of cells [49].…”
Section: Diverse Function Of Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%
“…Oxidative stress-induced DNA strand breaks activate the DNA repair enzyme poly(ADP-ribose) polymerase-1, which inactivates GAPDH by ADP-ribosylation and creating energy deficits and driving the cells towards accelerated cell death [48,49]. Thus, GAPDH relays the stress signals and regulates the ATP production to control the viable population of cells [49]. During apoptosis, GAPDH associates with the voltage dependent anion channel 1 and induces mitochondrial membrane permeabilization leading to the release of cytochrome c and apoptosis-inducing factor [50].…”
Section: Diverse Function Of Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%
“…In actively transcribed genes, it is shown that PARP1 acts to exclude histone H1 from their promoters, and thus a reciprocal binding between PARP1 and histone H1 may determine gene expression outcome (Krishnakumar et al 2008). Poly (ADP-ribosyl)ation can have different effects on various proteins including activation, downregulation, changes in protein confirmation, and promotion of protein-protein interactions (Zaniolo et al 2007, Hassa & Hottiger 2008, Devalaraja-Narashimha & Padanilam 2009). Thus, PARP1 exerts its effects via poly(ADPribosyl)ation, transcriptional regulation of gene expression, and transcription-related regulation of chromatin structure.…”
Section: Introductionmentioning
confidence: 99%